Evaluación de la intensidad de luz emitida por unidades de fotopolimerización utilizadas por estudiantes de la unidad de atención odontológica de la Unach - Garzón Rodríguez, Diana Carolina (2018)
The procedures with resinous materials at present are the most common processes in dentistry, since students and professionals do not give due importance to the process of photocuring of these materials. For this reason, the objective of this research was to evaluate the intensity of light emitted by photo polymerization units used by UAO students of the dental career of the National University of Chimborazo, through the use of a LITEX radiometer. An exploratory descriptive study of cross section to a universe of 98 light curing lamps was carried out, the variables included in this study were the photopolymerization lamps and the professional knowledge variable about the curing unit, including the photopolymerization time of the curing units. resinous materials. 36.7% of light-curing lamps had the right intensity, 36% of operators knew the correct time to light-cure resinous materials. 67.3% had resin residues in the fiber tip of the light curing units, the life time of the lamps were found in adequate standards. It was determined that the light intensity of the photopolymerization lamps of the UAO students register acceptable intensities. In spite of the higher percentage of light curing units that are not able to polymerize 63.3%, it generates alterations in the properties of the restorative material.